Does green banking affect banks’ profitability? - Mohammed K. Al-Kubaisi (17541636) (2023)
This paper empirically investigated the impact of green banking on the financial performance of Qatari banks. This paper collected the data for all banks in Qatar during the period 2012–2021. Specifically, the data collected included all 7 banks in Qatar and gathered data from the Refinitiv Eikon platform, the annual reports of the banks, and the relevant stock markets. Ordinary least squares (OLS) and panel regression have been applied but the fixed effect technique was interpreted because of the significance of the Hausman test. The dependent variable was the return on equity, the independent variables were size, loan loss provision, and two dummy variables as a proxy for green banking, which are: the availability of online banking and the availability of mobile applications. The results showed a positive relationship between the size and the return on equity and a negative relationship between the loan loss provision and the availability of mobile applications on the return on equity. The availability of online banking had an insignificant relationship with return on equity. This implies that larger Qatari banks tend to have larger profits and banks who estimate higher loan loss provisions are expected to have lower profitability. Surprisingly, the availability of mobile applications is found to affect profitability negatively if the cost of having the application is not covered by the noninterest charges. Other Information Published in: Journal of Governance and Regulation License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.22495/jgrv12i4art15